2013
DOI: 10.1177/1098214013512555
|View full text |Cite
|
Sign up to set email alerts
|

Who Is Afraid of Evaluation? Ethics in Evaluation Research as a Way to Cope With Excessive Evaluation Anxiety

Abstract: In this paper we share our reflections, as evaluators, on an evaluation where we encountered Excessive Evaluation Anxiety (XEA). The signs of XEA which we discerned were particularly evident amongst the program head and staff who were part of a new training program. We present our insights on the evaluation process and its difficulties, as well as our suggestions for coping with them. We suggest that signs of XEA and its consequences can be reduced by means of developing a detailed contract based on clear rule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…External supervisors work in a conflict-prone environment, and the very process of evaluation is an occasion for disagreement, where controversy may be the rule rather than the exception. 37 Anxiety may be expected and is to some extent beneficial in evaluation, yet in our data we find signs of so-called excessive evaluation anxiety, including conflict, avoidance, resistance, shame and anger, 17 , 18 which may all inhibit performance. While this is unpleasant for providers, such environment may also wear down evaluators in their aspirations for objective evaluations and respectful professional relations.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…External supervisors work in a conflict-prone environment, and the very process of evaluation is an occasion for disagreement, where controversy may be the rule rather than the exception. 37 Anxiety may be expected and is to some extent beneficial in evaluation, yet in our data we find signs of so-called excessive evaluation anxiety, including conflict, avoidance, resistance, shame and anger, 17 , 18 which may all inhibit performance. While this is unpleasant for providers, such environment may also wear down evaluators in their aspirations for objective evaluations and respectful professional relations.…”
Section: Discussionmentioning
confidence: 62%
“… 9 Evaluation has been described as the main manifestation of the supervisory power differential 15 and is a known source of tension and anxiety. 16 , 17 , 18 Studies on supervision in psychotherapy practice found strong yet complicated interactions between the practice of performance evaluation and quality of the supervisory relationship. 19 Supervisors carrying dual roles of performance evaluator and clinical supporter may find the trust from supervisees threatened if evaluations take place in the absence of basic mutual understanding.…”
Section: Introductionmentioning
confidence: 99%
“…XEA is a negative anxiety resulting from the evaluation process and experienced by evaluation participants including program staff. There are many ways in which XEA appears to have manifested itself in previous studies, including access issues, inaccurate data reporting, conflict, and reluctance to participate or cooperate (see also Bechar and Mero-Jaffe, 2014). The manifestation of evaluation anxiety in program settings is considered to be deeply unproductive, and can render 'evaluation data and findings worthless', and 'undermine the credibility of evaluators' (Donaldson et al, 2002, p.263).…”
Section: Challenges Facing Evaluationmentioning
confidence: 99%
“…9 Challenges can arise at virtually every stage—from the design of the evaluation through its conduct and eventual publication—to the extent that ‘evaluation anxiety’ is a known phenomenon. 10 Those being evaluated may be subjected to judgements about behaviour and outcomes against externally agreed targets. The detailed examination of individual, group and organisational practices may be experienced as risky and unpleasant, and strains in the relationships between the different parties may easily arise.…”
Section: Challenges In Conducting Programme Evaluationsmentioning
confidence: 99%